Laboratory of social innovation: creative hybridization between the social needs and significant experiences of students of business administration - Hernández-Gil, Cristian; Jaramillo-Gaitán, Fabio Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2020)
A qualitative investigation was carried out in the Business Administration Program of the University of the Amazonia, with students from the last semester. The objective was the application of a laboratory of social innovation, in the course of business ethics, to promote creative hybridization between the social needs of the city of Florencia and the significant learning of students. The methodological design used was action research in which seventy students participated who were chosen through non-probabilistic sampling. The results obtained were the invention of different prototypes that the subjects created from the problem posed in the laboratory. Most of these artifacts symbolized strength or power as the main element to raise awareness about respect for life. It is recommended to continue developing these training strategies, to promote in future professionals of administrative knowledge, skills that solve not only business but social difficulties, reinforcing teamwork, creativity and the ability to innovate.